Spectrophotometric Determination of Bisacodyl in Pure and Pharmaceutical Preparation via Oxidative Coupling Organic Reaction - Baghdad Science Journal (مجلة بغداد للعلوم)
A simple, accurate and sensitive spectrophotometric way is used to determine Bisacodyl in pure and pharmaceutical preparations. The proposed method depends on using 2,4-Dinitrophenylhydrazine as chromogenic reagent . The method was based on the oxidative coupling reaction of Bisacodyl with 2,4-Dinitrophenylhydrazine with Sodium periodate in the presence of sodium hydroxide as alkaline media to form red water soluble dye product , that has a maximum absorption at ?max 522nm . Beer ,s law is obeyed in the concentration of (2.00–20.00) ?g.ml -1 .The molar absorptivity is (6505) L.mol-1.cm-1,a sandall sensitivity of(0.0555) ?g.cm-2), correlation coefficient of (0.9970) , Limitof detection (LOD) (0.0312 ?g.ml-1), limit of Quantitation (LOQ) (0. 3125 ?g.ml-1) and the relative standard deviation of RSD% (1.6). The method gave a successful determination for Bisacodyl in pharmaceutical preparations and the value of recovery % was better than (100.16%)